2022
DOI: 10.1186/s40959-022-00142-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of miRNAs as biomarkers for chemotherapy-induced cardiotoxicity in breast cancer patients reveals potentially clinically informative panels as well as key challenges in miRNA research

Abstract: Breast cancer patients are at a particularly high risk of cardiotoxicity from chemotherapy having a detrimental effect on quality-of-life parameters and increasing the risk of mortality. Prognostic biomarkers would allow the management of therapies to mitigate the risks of cardiotoxicity in vulnerable patients and a key potential candidate for such biomarkers are microRNAs (miRNA). miRNAs are post-transcriptional regulators of gene expression which can also be released into the circulatory system and have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…Cardiotoxicity is one of the most significant complications among breast cancer patients as a result of the use of agents such as anthracyclines and monoclonal antibodies directed against HER2. Therefore, the search for prognostic biomarkers of this event is crucial in mitigating the risk of cardiotoxicity in vulnerable patients [ 203 , 204 ]. Numerous microRNAs are considered among the candidates, including hsa-miR-1273 g-3p and hsa-miR-4638-3p (regulating TGF-β and CTGF pathways, responsible for atherosclerotic plaque instability and heart failure [ 205 ]), hsa-miR-208 (associated with fibrosis and EMT progression, and specifically targeted to the BMP co-receptor, endoglin [ 206 , 207 ]), hsa-miR-130a (associated with cardiomyopathy [ 208 , 209 , 210 ]), hsa-miR-29a (involved in hemolysis of blood cells [ 211 , 212 ]) or proangiogenic hsa-miR-17-5p, hsa-miR-19a, hsa-miR-378, hsa-Let-7b [ 208 , 209 ] and hsa-miR-126 [ 207 , 211 ].…”
Section: The Role Of Mirnasmentioning
confidence: 99%
“…Cardiotoxicity is one of the most significant complications among breast cancer patients as a result of the use of agents such as anthracyclines and monoclonal antibodies directed against HER2. Therefore, the search for prognostic biomarkers of this event is crucial in mitigating the risk of cardiotoxicity in vulnerable patients [ 203 , 204 ]. Numerous microRNAs are considered among the candidates, including hsa-miR-1273 g-3p and hsa-miR-4638-3p (regulating TGF-β and CTGF pathways, responsible for atherosclerotic plaque instability and heart failure [ 205 ]), hsa-miR-208 (associated with fibrosis and EMT progression, and specifically targeted to the BMP co-receptor, endoglin [ 206 , 207 ]), hsa-miR-130a (associated with cardiomyopathy [ 208 , 209 , 210 ]), hsa-miR-29a (involved in hemolysis of blood cells [ 211 , 212 ]) or proangiogenic hsa-miR-17-5p, hsa-miR-19a, hsa-miR-378, hsa-Let-7b [ 208 , 209 ] and hsa-miR-126 [ 207 , 211 ].…”
Section: The Role Of Mirnasmentioning
confidence: 99%
“…We have already mentioned the role of miRNAs in predicting response to chemotherapy [ 60 ], but can miRNAs be useful in predicting cardiotoxicity? One systematic review identified a range of miRNAs as markers of cardiac damage in breast cancer patients treated with chemotherapy, highlighting the important role of these molecules in side effect management [ 109 ]. Traditional biomarkers of cardiac function include natriuretic peptides [ 110 ] and troponin levels [ 111 ].…”
Section: Implications Of Breast Cancer Therapies On Cardiovascular Fu...mentioning
confidence: 99%
“…Moreover, in vitro data cannot reliably describe the complex changes which develop slowly in clinical settings over many weeks or months. Indeed, several rodent in vivo studies as well as clinical trials have been performed in the past few years (see the review of Piegari et al, 2016 ; Ruggeri et al, 2018a ; Pereira et al, 2020 ; Chen and Xu, 2021 ; Brown et al, 2022 ). However, these studies have typically only concentrated on a few “cardiac enriched” miRNAs (e.g., miR-208, miR-1, and miR-133), while the presented results have been highly variable, possibly due to differences in dosage schedules, ANT administration, and the duration of the treatment ( Nishimura et al, 2015 ; Oliveira-Carvalho et al, 2015 ; Rigaud et al, 2017 ; Alves et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies have typically only concentrated on a few “cardiac enriched” miRNAs (e.g., miR-208, miR-1, and miR-133), while the presented results have been highly variable, possibly due to differences in dosage schedules, ANT administration, and the duration of the treatment ( Nishimura et al, 2015 ; Oliveira-Carvalho et al, 2015 ; Rigaud et al, 2017 ; Alves et al, 2022 ). A systematic review of the miRNAs that are currently used as plasma biomarkers for chemotherapy-induced cardiotoxicity in breast cancer patients suggest that three miRNA markers (miR-29a, miR-34a and miR-423) can be used as general cardiotoxicity indicators but should be supplemented with data concerning miR-1, miR-499 and miR-122 for patients receiving doxorubicin ( Brown et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%